Integrasi Ilmu Dan Agama Universitas Islam Negeri Sunan Kalijaga - Kosa, Hikmah Akmelia; Irawan, Irawan (Yayasan Cendekia Gagayunan Indonesia, 2025)
The emergence of discussions on the issue of integration of science to the surface is actually an effort to examine the dynamics of life and dichotomous science in the Islamic world. Efforts to integrate and interconnect various Islamic sciences with science are efforts and at the same time as an urgent answer to the weaknesses and deficiencies among Muslims compared to the paradigm of Western science. For centuries, Muslims have been imprisoned in a narrow and irrational understanding of religion. As if studying the universe is not a religious act. There is a strict separation between worldly affairs and the hereafter, between science and religion, between scientists and scholars. Consequently, the Islamic world is far behind the progress of Western science. Aware of the limitations of the impact and slap of Western science, knowledge and technology, PTAI throughout Indonesia are improving themselves, making serious changes and changes. The change of STAIN to IAIN and the conversion of IAIN to UIN still leaves big, complicated and complex problems, especially in the issue of developing the paradigm of integration of science, pillars of spirituality and its implementation model. The development model of the science integration paradigm developed at UIN Suka Yogyakarta is concentrated on the spider web symbol.